INVESTIGATION OF ENDOTHERMIC PROPERTIES OF INDUSTRIAL WASTES - Aigul Naukenova ,; B. Sapargaliyeva,; J. R. Ilarri,; Sh. Shapalov,; Z. Kerimbekova,; G. Kenzhaliyeva, (Academic Journal of Physical and Chemical Sciences, 2019)
At the present time the applied fire-extinguishing standard compositions are very expensive and therefore are perspective investigation of fire-extinguishing properties of the pulverized industrial waste. This is connected with their cheapness, low expenses for initial reworking and possibility of their utilization. At the analysis carrying out of patent and scientific-technical literatures on the question of presence the fireextinguishing powders it was identified that basic powder components are in non-combustible metallurgic waste. The searching of effective flash suppressors with waste using is rational in the direction of complex compositions development having low temperatures of endothermic processes of melting, decomposition or evaporation with inert gases formation, but for easy-flammable powders are many-component eutectic mixtures. There are investigated more than 250 minerals and mountain rocks in order to identify endothermic effects. The following ones have endothermic effects in the field of low temperatures: СаСОз • MgCO.3- dolomite; СаСОз - calcite, aragonite; MgC03- magnesite; Са (Mg, Fe) (С03) 2 - ankerite; Na2 S04• 10Н2О - mirabolite; А1 (ОН)3 + А14[Si40|o] • (ОН)8 –boxite.